Clinical Characteristics and Outcome of Children With Relapsed Medulloblastoma: A Retrospective Study at a Single Center in China. Issue 8 (November 2018) - Du, Shuxu; Yang, Shuli; Zhao, Xia; Xiao, Jiang; Ren, Siqi; Li, Shuting; Zhang, Jin; Wang, Yuan; Gong, Xiaojun; Li, Miao; Sun, Yanling; Wu, Wanshui; et al.
Abstract : Relapsed medulloblastoma (MB) has a dire prognosis, and chemotherapy remains the main therapeutic option. We retrospectively analyzed the clinical characteristics and survival rates of 60 Chinese children with relapsed MB. The patients received 11 cycles of chemotherapy in sequence, followed by 12 cycles of oral temozolomide and etoposide. Thirty patients were simultaneously administered intrathecal methotrexate (IT-MTX). The Kaplan-Meier method was used to determine survival rates; the patients' median survival time after relapse was 2.8 years, 5-year progression-free survival (PFS) and overall survival (OS) rates were 26.7%±5.7% and 31.6%±6.9%, respectively. There was no significant difference between these rates according to histology or molecular subgroup. Tumor cells were detected in the cerebrospinal fluid of over 40% of patients; such patients had significantly shorter OS and PFS rates. Patients who received IT-MTX showed significantly longer survival than those who did not (3.73 vs. 2.06 y, respectively, P =0.000); the corresponding 5-year PFS and OS rates were 43.3%±9.0% versus 10.0%±5.5% and 49.5%±11.1% versus 14.6%±6.9%, respectively ( P =0.000). In addition, tumor cell-positive cerebrospinal fluid and IT-MTX use significantly influenced PFS and OS in relapsed patients. Taken together, our data show that IT-MTX improves the survival of patients with relapsed MB.